2018
DOI: 10.18280/ijht.360411
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the calculated and experimental dependencies of the combustion of coal dust on the basis of a new methodological base of theoretical studies of heat exchange processes

Abstract: The methodology of theoretical studies of heat exchange processes in boiler units based on the mathematical model of burning coal dust has been developed. For the first time, the continuous curve of the fractional composition of an ensemble of coal particles is presented. The mathematical model is consistent with the aeromechanical and thermal characteristics of the torch, obtained on the basis of calculated and experimental data. The concept of a torch continuum is introduced as a continuous medium in which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…In their early works, the authors of the article presented the results of research on the operation of boiler units and heat and power equipment. For example, in [32] Toropov et al presented new methods for studying the operation of boiler units, and in [33] E.V. Toropov et al showed the possibility of organizing new methods in a new methodological framework.…”
Section: Experimental Datamentioning
confidence: 99%
“…In their early works, the authors of the article presented the results of research on the operation of boiler units and heat and power equipment. For example, in [32] Toropov et al presented new methods for studying the operation of boiler units, and in [33] E.V. Toropov et al showed the possibility of organizing new methods in a new methodological framework.…”
Section: Experimental Datamentioning
confidence: 99%
“…Their traditional areas of application are technical and mathematical disciplines, for example, automatic control theory, information and signal transmission theory, equations of mathematical physics, differential equations etc. Similar developments were proposed by the authors in the field of power engineering [22,23]. Besides, the authors initially developed a mathematical apparatus for approximating piece linear functions [24,25].…”
Section: F the Use Of Piece Linear Functions For Signal Samplingmentioning
confidence: 83%
“…Mathematical models are employed to describe time series [23]. Imagine that the time series x τ generated by some model can be represented as two components…”
Section: B Model Adaptation Based On the New Data Sampling Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be borne in mind that the combination of such derivatives forms the organizational and technical tools for the mechanism for regulating the resulting indicator-property of energy efficiency of non-stationary heat transfer processes of the studied heat engineering element and heat power plant in the phase of high-tech organizational and innovative dynamics [20,21]. The evolutionary, spasmodic, bifurcation, lowefficiency, degrading nature of heat transfer processes, of course, must comply with the second and other laws of thermodynamics [22][23][24]:…”
Section: H X a A A A A A A A A A Xmentioning
confidence: 99%